Savouring health and well-being: the pomegranate prescription / Dr. Mohd Izani Othman - Othman, Mohd Izani (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Pomegranate (Punica granatum), locally known as delima, stands as a botanical treasure renowned for its diverse applications in medicinal contexts. Its historical presence is marked in ancient manuscripts, including Babylonian literature, the Book of Exodus, the Homeric Hymns, and the Quran, attesting to its significant medicinal and culinary uses. The etymology of the word "pomegranate" traces back to the Medieval Latin words "pomum" (meaning "apple") and "granatum" (meaning "seeded"). Cultivated primarily in the Middle East and Mediterranean regions, this small tree and its fruit play a pivotal role in traditional practices, flourishing in hot and arid climates to yield the iconic, ruby-red bounty. Comprising various parts, including seeds, peels, pulp, and juice, each component contributes to its multifaceted utility. Pomegranates have been recognised for innumerable health benefits, with implications in disease cure acknowledged since ancient times.